2014
DOI: 10.1097/rct.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Dynamic Susceptibility Contrast MR Perfusion Maps Generated by Different Methods Implemented in Commercial Software

Abstract: The use of a different software application determines different results, even if the algorithms seem to be the same. The introduction of AIF in the data postprocessing determines a higher estimates variability that can make interhospital and intrahospital examinations not completely comparable. A simpler approach based on raw curve analysis produces more stable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…Specifically, use of a preload of contrast agent, and a flip angle less than 90° is proving to be one of the most accurate approaches, further confirmed by two recent studies [19, 41], both incorporating sophisticated simulations of DSC-MRI data representative of brain tumor. Use of a preload might also be an important reason why greater consistency across post-processing methods was found in this study compared to previous studies (eg [32]). Collecting DSC-MRI data after preload was shown to decrease the dependence of tumor rCBV on the chosen method of analysis [20].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Specifically, use of a preload of contrast agent, and a flip angle less than 90° is proving to be one of the most accurate approaches, further confirmed by two recent studies [19, 41], both incorporating sophisticated simulations of DSC-MRI data representative of brain tumor. Use of a preload might also be an important reason why greater consistency across post-processing methods was found in this study compared to previous studies (eg [32]). Collecting DSC-MRI data after preload was shown to decrease the dependence of tumor rCBV on the chosen method of analysis [20].…”
Section: Discussionmentioning
confidence: 58%
“…For example, in one study [32] two commercial software packages (NordicICE (NordicNeuroLab, Bergen, Norway)) and GE Brainstat (GE Healthcare, Milwaukee, WI)) were compared. Like the present study, one dataset of 24 patients with de novo glioblastoma was used and ROIs of tumor and reference brain were pre-determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, rCBV, as measured on IBNeuro, showed stronger correlation with image-guided microvessel quantification and higher accuracy in predicting tumor recurrence from pseudoprogression/radiation necrosis, based on validation by surgical histologic tumor quantification. Orsingher et al (26) also found significant differences in rCBV values when comparing General Electric and NordicICE software packages. The findings of both these studies coincide with the findings of the current study.…”
Section: Discussionmentioning
confidence: 94%